Ports maritimes flamands, complexe portuaire liégeois et port de Bruxelles - Rapport 2008 - Claude Mathys (National Bank of Belgium, 2010)
– This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Oostende, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centres facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels in the period 2003 - 2008, with an emphasis on 2008. Focusing on the three major variables of value added, employment and investment, the report also provides some information about social balance and the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. In terms of maritime cargo traffic, 2008 was another good year for all the Flemish sea ports, despite the downturn recorded during the last quarter of the year. Except for Ghent, direct value added rose in all the ports in Flanders. Maritime branches as a whole expanded, but the non-maritime branches of trade and industry contracted. The ports of Zeebrugge and Ostend enjoyed growth in both maritime and nonmaritime branches, while in Antwerp and Ghent, the non-maritime branches declined. In Antwerp, however, the growth in direct value added in the maritime branches was particularly high, unlike the port of Ghent. Direct employment rose slightly during the year 2008. Again, direct employment in the maritime branches as a whole increased, whereas it declined in trade and industry. Nonetheless, a rise in employment was reported in all the Flemish ports apart from Antwerp. After the growth of 2007, investment declined marginally in the Flemish ports across the board. The ports of Antwerp, Ostend and Ghent recorded higher investment in 2008. Thanks to the port of Antwerp's shipowners, the rise was concentrated in the maritime branches, whereas the non-maritime branches as a whole declined, due to the downturn in the Antwerp region. In the other ports, investment in the non-maritime branches expanded. The volume of cargo handled in the port of Liège increased again in 2008. Direct value added and employment registered strong growth. Due to the metalworking and energy sectors, employment improved on the previous year's figures. Fuel production and the chemicals industry accounted for the growth in value added. Investment rose strongly, too. A major factor behind this increase was the construction of a new bioethanol plant in Wanze and a waste treatment plant in Herstal. At the end of the year, ArcelorMittal decided to shut down blast furnace n°6 in Seraing, a decision that will have an impact on the activity in the port of Liège. The volume of cargo handled at the port of Brussels rose again in 2008. Value added in this port increased and employment remained steady. After falling back in 2007, investment picked up thanks to the infrastructure renovation work undertaken by the port authority on the former Carcoke site. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2008
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments